Inhibition of arabidopsis hypocotyl elongation by jasmonates is enhanced under red light in phytochrome B dependent manner - Chen, Jing (Springer Japan, 2012)
Jasmonates are phytohormones derived from oxygenated fatty acids that regulate a broad range of plant defense and developmental processes. In Arabidopsis, hypocotyl elongation under various light conditions was suppressed by exogenously supplied methyl jasmonate (MeJA). Moreover, this suppression by MeJA was particularly effective under red light condition. Mutant analyses suggested that SCF(COI1)-mediated proteolysis was involved in this function. However, MeJA action still remained in the coi1 mutant, and (+)-7-iso-JA-L-Ile, a well-known active form of jasmonate, had a weaker effect than MeJA under the red light condition, suggesting that unknown signaling pathway are present in MeJA-mediated inhibition of hypocotyl elongation. EMS mutant screening identified two MeJA-insensitive hypocotyl elongation mutants, jasmonate resistance long hypocotyl 1 (jal1) and jal36, which had mutations in the phytochrome B (PHYB) gene. These analyses suggested that inhibition of hypocotyl elongation by jasmonates is enhanced under red light in phyB dependent manner. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10265-012-0509-3) contains supplementary material, which is available to authorized users.